Anterior Insula–Associated Social Novelty Recognition: Pivotal Roles of a Local Retinoic Acid Cascade and Oxytocin Signaling - Kim, Sun-Hong; An, Kyongman; Namkung, Ho; Saito, Atsushi; Rannals, Matthew D.; Moore, James R.; Mihaljevic, Marina; Saha, Sneha; Oh, Seyun; Kondo, Mari A.; Ishizuka, Koko; Yang, Kun; et al. (The American journal of psychiatry, 2023)
Objective:Deficits in social cognition consistently underlie functional disabilities in a wide range of psychiatric disorders. Neuroimaging studies have suggested that the anterior insula is a “common core” brain region that is impaired across neurological and psychiatric disorders, which include social cognition deficits. Nevertheless, neurobiological mechanisms of the anterior insula for social cognition remain elusive. This study aims to fill this knowledge gap.Methods:To determine the role of the anterior insula in social cognition, the authors manipulated expression of Cyp26B1, an anterior insula-enriched molecule that is crucial for retinoic acid degradation and is involved in the pathology of neuropsychiatric conditions. Social cognition was mainly assayed using the three-chamber social interaction test. Multimodal analyses were conducted at the molecular, cellular, circuitry, and behavioral levels.Results:At the molecular and cellular level, anterior insula–mediated social novelty recognition is maintained by proper activity of the layer 5 pyramidal neurons, for which retinoic acid–mediated gene transcription can play a role. The authors also demonstrate that oxytocin influences the anterior insula–mediated social novelty recognition, although not by direct projection of oxytocin neurons, nor by direct diffusion of oxytocin to the anterior insula, which contrasts with the modes of oxytocin regulation onto the posterior insula. Instead, oxytocin affects oxytocin receptor–expressing neurons in the dorsal raphe nucleus, where serotonergic neurons are projected to the anterior insula. Furthermore, the authors show that serotonin 5-HT2C receptor expressed in the anterior insula influences social novelty recognition.Conclusions:The anterior insula plays a pivotal role in social novelty recognition that is partly regulated by a local retinoic acid cascade but also remotely regulated by oxytocin via a long-range circuit mechanism.